Integrating omics approaches in livestock biotechnology: innovations in production and reproductive efficiency - Wadood, Armughan Ahmed; Bordbar, Farhad; Zhang, Xiquan (Frontiers in Animal Science, 2025)
Current achievements in omics technologies have modernized livestock biotechnology, offering extraordinary comprehension of animal productivity, health, and reproduction. This extensive study examines the integration and implementation of the omics approaches, genomics, transcriptomics, proteomics, metabolomics, and epigenomics in livestock production systems. We reconnoitered how genomic novelties redesign breeding strategies with marker-assisted selection and CRISPR-based gene editing. Together, transcriptomic analyses indicate key insights into gene expression patterns governing economically essential traits such as muscle growth and milk production. This study also shows the role of proteomics in identifying biomarkers for health surveillance and product quality improvement along with metabolomics, which contributes to understanding feed efficiency and disease resistance. Particular attention is given to epigenomics studies exploring DNA methylation and histone modifications in reproductive efficacy, underlining their importance in fertility and embryonic development. Integrating multi-omics data through systems biology approaches is discussed, demonstrating its perspective in evolving precision livestock production. We also observed how omics technologies improve assisted reproductive technologies (ART) by better understanding of molecular mechanisms underlying fertility and embryo development. While acknowledging the potential of these technologies, we discuss critical challenges, data integration complications, and ethical respect for genetic modification. This review outlines prospect directions and potential novelties in livestock biotechnology, highlighting the crucial role of omics approaches in addressing global food security contests through better livestock productivity and reproductive efficiency. This study suggests that continuous improvement in omics technologies might be the underlying cause of the determination of the future of sustainable livestock production.